Reasons behind social stigmatization of the person with disabilities in Sri Lanka: A study in the Northern Province, Sri Lanka - Luxshe, H.; Anutharsi, G. (Parliment of Sri Lanka, 2022)
This study has identified the reasons for social stigmatization of the people with disabilities living in Northern, Sri Lanka. The thirty-year war in Sri Lanka ended in 2009. As a result, the number of people with disabilities in the society has increased. They experience various problems and suffer negative consequences. The war has created 15% of the people with disabilities in the Northern Province of Sri Lanka. In that way, this study has been based on the Maritimepattu DS Division, Mullaitivu District, where the final battle took place. The main objective of the study is to find out the causes of social stigmatization faced by the war disabled people. Its sub-objectives include the followings: to identify the social stigmatization faced by war affected members and to make recommendations to reduce them. For this both quantitative and qualitative research methods have been used. Physically disabled people have been selected as the sampling of this research. Fourty questionnaires and ten case studies were used to collect data of this study. Data analysis has been done through MS Excel and thematic analysis method. People with disabilities face social stigmatization. Socio-cultural, economic and infrastructural, political and health reasons are behind for the social stigmatization of the war disabled in the research area. Lack of accessibility for persons with disabilities, prejudice based on religion and superstitions cause their stigma. People with disabilities are also pointed by calling them various names. They labelled as sothi, kurudu, mudam, sevidu, nondi, oomai, by the society. They feel that they are discriminated against by the society. The sudden onset of war has put them differently abled category. As a result, they feel huge differences in their social status, the way people look at them, and the respect others give them. Even though rights and laws are having kind of supportive, but the socio- cultural factors stand behind to give equal status to the disabled people even not properly treat them as human beings in the society. As a result, people with disabilities have to spend their lives inhouse, despite the desire to progress. In many cases even family members and community members who think that they are helping them and don't let them do any activity on their own lead to the formation of social stigma for the disabled people. Through the process of socialization culturally those can be freed from the marginalization they experience. Mainly, people with disabilities inclusivity, proactive skills development, family counseling can help them to move forward from the causes of social stigmatization.
Keywords: Persons with disability; Stigmatization; Reason; Labelled; Discrimination